Evaluasi Kelembagaan Kota Samarinda Berdasarkan Kebijakan Penataan Kelembagaan Pemerintah Daerah : Studi Kasus pada Dinas Kesehatan Kota Samarinda - Sartika, Dewi; rustan amarullah; Kemal Hidayah; Fani Heru Wismono; MARIA AGUSTINI PERMATA SARI; Mayahayati Kusumaningrum; Tri Noor Aziza; Tri Wahyuni; Novi Prawitasari; Ricky Noor Permadi (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2023)
Changes in the dynamic strategic and regulatory environment are challenges as well as opportunities for city governments to formulate and formulate organizational policies that are in line with the direction of development. The arrangement of regional apparatus organizations is a common thing in an organizational cycle, including in local government organizations. With the simplification of the regional government organization, it is hoped that the performance of the local government will become more effective and efficient. Institutional arrangements are not limited to nomenclature, but also have an impact on coordination governance, scope of work, resource management, and so on. By using institutional arrangement criteria from a budgeting policy perspective, analyzing the value of strategic issues related to regional vision and mission as well as regional flagship programs, analysis of regional institutional models and nomenclature, analyzing the typology of affairs, which are then offered into two models, namely: 1) Progressive Institutional Model and 2) Pragmatic Institutional Model. In short, differences from alternative institutional models fundamentally change existing institutions, but still prioritize key factors in achieving local government goals. On the other hand, the choice of the pragrammatic model represents a moderate, realistic, and rational institutional model, but the two alternative models still offer a more streamlined structure and a more efficient allocation of resources. It is possible to choose a hybrid model, taking into account the intensity of the workload, and optimize the performance of the flagship program.